Strategies for e-business : concepts and cases on value creation and digital business transformation / Tawfik Jelassi; Francisco J Martínez López - Jelassi, Tawfik, 1957-
This is the fourth edition of a unique textbook that provides extensive coverage of the evolution, the current state, and the practice of e-business strategies. It provides a solid introduction to understanding e-business and e-commerce by combining fundamental concepts and application models with practice-based case studies. An ideal classroom companion for business schools, the authors use their extensive knowledge to show how corporate strategy can imbibe and thrive by adopting vibrant e-business frameworks with proper tools. Students will gain a thorough knowledge of developing electronic and mobile commerce strategies and the methods to deal with these issues and challenges.